Ball grid array-module with integrated shaped lens for WiGig applications in eyewear devices - Bisognin, A.; Cihangir, A.; Luxey, C.; Jacquemod, G.; Pilard, R.; Gianesello, F.; Costa, J. R.; Fernandes, C. A.; Lima, E. B.; Panagamuwa, C.; Whittow, W. (IEEE Transactions on Antennas and Propagation, 2016)
A ball grid array-module (BGA-module) incorporating a low-cost shaped dielectric lens is proposed for wireless communications in the 60-GHz WiGig band between a smart eye-wear, where it is integrated and facing a laptop or TV. The module, which is codesigned with a 60-GHz transceiver, consists of two separate identical antennas for transmitting (Tx) and receiving (Rx). The in-plane separation of these elements is 6.9 mm both being offset from the lens focus. This poses a challenge to the lens design to ensure coincident beam pointing directions for Rx and Tx. The shaped lens is further required to narrow the angular coverage in the elevation plane and broaden it in the horizontal plane. A 3-D-printed eyewear frame with an integrated lens and a recess for proper BGA-module integration is fabricated in ABS-plastic material. Measurements show a reflection coefficient below -12 dB in the 57-66 GHz band. A maximum gain of 11 dBi is obtained at 60 GHz, with 24 degrees and 96 degrees beamwidth at 5-dBi gain, respectively, in the vertical and horizontal planes. The radiation exposure is evaluated for a homogeneous SAM head phantom and a heterogeneous visible human head. The simulated power density values for both models are found to be lower than the existing standards.